Peningkatan Budaya Literasi Dasar Melalui Pojok Baca MI Roudlatul Ulum Cendekia Bantur - Sumarno Aziz; Salim; Nanik Ulfa; Yan Rahmawati; Hasan Bisri; Aldi Sallam, Dimas (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2022)
Literacy is one of the cultures that must be applied in the world of education, especially at the SD/MI level. Literacy or reading needs to be familiarized, is a process of making something that makes a person accustomed, in terms of teaching methods, it can be said that habituation is a way that can be done to get students used to thinking. The literacy culture embedded in students affects the level of success and the ability of students to understand analytical, critical, and reflective information. The function of the reading corner is to familiarize students with increasing literacy culture, besides that it is expected to reduce noise during breaks or can also be an alternative learning method used by educators in the learning process. The type of literacy chosen in this activity is basic literacy, in making the literacy corner it refers to literacy principles including the principle of balance, the importance of spoken language, taking place in a curriculum, the importance of diversity. With the literacy corner at MI Roudlatul Ulum Cendekia, it is hoped that it can improve the literacy culture that has been built previously.